Pengaruh Lingkungan terhadap Minat Sekolah Anak Usia 7 Sampai Dengan 15 Tahun di Kenagarian Sialang Gaung - saputra, ridho (Jurnal Sakinah, 2021)
The study was based on children aged 7 to 15 years in Kenagarian Sialang Gaung who decided to quit school due to environmental influence factors. This study aims to find out the influence of the environment on the school interests of children aged 7 to 15 years in Kenagarian Sialang Gaung. The use of methods is done with descriptive quantitative approaches and is assisted by observation, interview, and custodian techniques as data collection techniques. Analytical techniques use simple linear regression. The results showed an environmental influence on school interest in dropouts aged 7 to 15 year in Kenagarian Sialang Gaung.